2010
DOI: 10.1523/jneurosci.0487-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Correlate of Impaired Covert Visual Attentional Processes in Patients with Cerebellar Lesions

Abstract: In the past years, claims of cognitive and attentional function of the cerebellum have first been raised but were later refuted. One reason for this controversy might be that attentional deficits only occur when specific cerebellar structures are affected. To further elucidate this matter and to determine which cerebellar regions might be involved in deficits of covert visual attention, we used new brain imaging tools of lesion mapping that allow a direct comparison with control patients. A total of 26 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 51 publications
3
27
0
Order By: Relevance
“…In contrast to our study, previous VH convergence studies have used matching tasks, in which participants were required to match inputs from the same or different modalities. In the case of different modalities, this might have imposed additional processing load regarding memory processes or attention which might have influenced the mechanisms of VH convergence (Holdstock et al, 2009; see also van Atteveldt et al, 2007;Baier et al, 2010). Our study suggests that in the absence of such task effects VH convergence can be found not only in the LOC but also in bilateral regions of the anterior cerebellum.…”
Section: Discussionmentioning
confidence: 69%
“…In contrast to our study, previous VH convergence studies have used matching tasks, in which participants were required to match inputs from the same or different modalities. In the case of different modalities, this might have imposed additional processing load regarding memory processes or attention which might have influenced the mechanisms of VH convergence (Holdstock et al, 2009; see also van Atteveldt et al, 2007;Baier et al, 2010). Our study suggests that in the absence of such task effects VH convergence can be found not only in the LOC but also in bilateral regions of the anterior cerebellum.…”
Section: Discussionmentioning
confidence: 69%
“…Indeed, the physiology of the cerebellum suggests that translated to the attentional system, this same internal model system may be responsible for predictive deployment and maintenance of attention. There is evidence of the cerebellum contributing to attentional processes from imaging, transcranial magnetic stimulation and lesion studies (Brissenden et al, 2016; Arasanz et al, 2012; Baier et al, 2010). Thus, it is plausible that the iTBS-induced improvement in sustained attention may arise from improved functioning of the cerebellum’s role in attention.…”
Section: Discussionmentioning
confidence: 99%
“…The ineffectiveness of VS adaptation in boosting covert exogenous attention is also consistent with VS adaptation-dependent recruitment of a more dorsal parietal network, centred over the intra-parietal sulcus (Gerardin et al, 2012 ; Panouillères et al, 2014 ), which has been previously involved in endogenous attention [Lateral Intra-Parietal area in monkey (Wardak et al, 2004 ; Balan and Gottlieb, 2009 ); Intra-Parietal Sulcus in humans (Jerde et al, 2012 )]. In summary, this model provides a parsimonious framework for linking these behavioral findings to their possible neural underpinnings, which by no means excludes the contribution of other brain areas involved both in covert attention [e.g., Frontal Eye Fields (Moore and Fallah, 2001 ); Superior Colliculus (Zénon and Krauzlis, 2012 ; Katyal and Ress, 2014 ); cerebellar vermis (Baier et al, 2010 )] and saccadic adaptation (see Hopp and Fuchs, 2004 ; Iwamoto and Kaku, 2010 ; Jenkinson and Miall, 2010 ; Pélisson et al, 2010 ; Prsa and Thier, 2011 ).…”
Section: Discussionmentioning
confidence: 99%